AN ASSESSMENT OF THE ROLE OF MASS MEDIA DURING THE PEOPLE’S DEMOCRATIC PARTY RULE IN NIGERIA (1999-2015) - Obasi, Ferdinard; Phoebe Nzurumike, Chimdiadi (African Journal of Social and Behavioural Sciences, 2026)
Nigeria’s media landscape shifted significantly when democratic rule was restored in 1999, ending years of military control. This study examines the role of the mass media in Nigeria’s democratic consolidation during the People’s Democratic Party’s 16-year rule, from 29 May 1999 to 29 May 2015. It tests the liberal democratic claim that expanded press freedom automatically strengthens accountability. Using desk research and content analysis of laws, NBC data, academic literature, and NGO reports, the paper applies Agenda-Setting Theory, Social Responsibility Theory, and Political Economy of the Media to assess media performance. Findings reveal that legal-institutional reforms were substantial: Section 39 of the 1999 Constitution restored free expression, the NBC licensed 147 private radio and TV stations, and the 2011 Freedom of Information Act gave journalists statutory access to records. Digital platforms after 2010 further broadened public debate, with #OccupyNigeria and #BringBackOurGirls illustrating citizen-led agenda-setting. Media exposure of corruption rose by 40% between 2011 and 2014. Yet watchdog outcomes were limited. Of 312 major corruption cases reported from 1999–2015, only 7.7% ended in conviction. Political economy constraints persisted: 11 of 15 national dailies had links to political financiers; 60–70% of newspaper revenue came from government advertising; the NBC issued 147 fines and 12 closures, 81% targeting political content; and 74% of journalists earned below N50,000 monthly, entrenching brown envelope practice. The study concludes that Nigeria experienced “liberalization without independence.” The media gained agenda-setting power and could mobilize against policies like the Third Term bid, but could not ensure sanctions. The paper recommends media funding reform, narrower NBC powers, stronger FOI enforcement, journalist welfare standards, and institutional synergy between media and anti-graft bodies.